2012
DOI: 10.1371/journal.pone.0030860
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Copy Number Variants Suggests LTBP1 and FGD4 Are Important for Alcohol Drinking

Abstract: Alcohol dependence (AD) is a complex disorder characterized by psychiatric and physiological dependence on alcohol. AD is reflected by regular alcohol drinking, which is highly inheritable. In this study, to identify susceptibility genes associated with alcohol drinking, we performed a genome-wide association study of copy number variants (CNVs) in 2,286 Caucasian subjects with Affymetrix SNP6.0 genotyping array. We replicated our findings in 1,627 Chinese subjects with the same genotyping array. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A 95% Bayesian credible interval was calculated for all meta-mQTLs and these intervals were input into the UCSC LinkOver tool to map the mouse (mm9) genome location to the human (hg19) genomic location (http://genome.ucsc.edu/cgi-bin/hgLiftOver). Various alcohol related phenotype GWAS [42], [43], [44], [45], [46] were examined for any associated SNPs residing within the syntenic region of the mQTLs. Knowledge-based searches on these syntenic regions were used for comparative genomics.…”
Section: Methodsmentioning
confidence: 99%
“…A 95% Bayesian credible interval was calculated for all meta-mQTLs and these intervals were input into the UCSC LinkOver tool to map the mouse (mm9) genome location to the human (hg19) genomic location (http://genome.ucsc.edu/cgi-bin/hgLiftOver). Various alcohol related phenotype GWAS [42], [43], [44], [45], [46] were examined for any associated SNPs residing within the syntenic region of the mQTLs. Knowledge-based searches on these syntenic regions were used for comparative genomics.…”
Section: Methodsmentioning
confidence: 99%
“…For example, we reported that 754,259 (75%) among one million SNPs were significantly (p<10 −8 ) different in allele frequency between European-Americans and African-Americans; and the minor alleles ( f <0.5) of 157,718 (16%) SNPs in European-Americans were the major alleles ( f >0.5) in African-Americans, and vice versa [see Supplemental Materials and Methods by Zuo et al (Zuo et al, 2012)]. Suppose the causal allele of a putative disease-causal variant is a minor allele, it is expected that the risk allele of a marker in complete linkage disequilibrium (LD) with this causal allele would be a minor allele too, although this minor allele may be in opposite phases between European-Americans and African-Americans if this marker is among those 157,718 SNPs (Pei et al, 2012, Zuo et al, 2012). The combined effects of the same allele of such a marker (i.e., rare in one population but common in another) across these two populations by meta-analysis will be neutralized, which results in information loss.…”
Section: Introductionmentioning
confidence: 99%
“…194 In addition to the single SNP-based GWAS for AD and alcohol-related phenotypes, one genomewide gene set-based analysis 153 and three genomewide studies of copy number variants (CNVs) have been published to date (Table 4). 151,166,169 CNVs are a form of structural variation in which large regions of the genome are duplicated or deleted. CNVs, which are often rare, have been shown to explain a proportion of the risk for schizophrenia and autism.…”
Section: Gwas Of Ad or Symptoms Of Admentioning
confidence: 99%